2017
DOI: 10.1111/bjd.15697
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and molecular characterization of actinic lentigos reveals alterations of the dermal extracellular matrix

Abstract: Drastic disorganization of the cutaneous structure in AL is accompanied by a specific molecular signature revealing alterations in both epidermal and dermal compartments. In particular, our results suggest that local modifications of the dermal extracellular matrix might contribute to hyperpigmentation in AL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 56 publications
4
24
0
Order By: Relevance
“…It is frequently found on photoexposed areas such as the hand, face, and upper back. Histological observations confirmed that melanin accumulates in the actinic lentigo epidermis mostly in the basal layer [ 309 , 310 , 311 ]. Such lentigo is also characterized by deep epidermal invaginations that form club-shaped or bud-like extensions into the dermis.…”
Section: Mid- and Long-term Consequences Of Uv Exposurementioning
confidence: 75%
See 1 more Smart Citation
“…It is frequently found on photoexposed areas such as the hand, face, and upper back. Histological observations confirmed that melanin accumulates in the actinic lentigo epidermis mostly in the basal layer [ 309 , 310 , 311 ]. Such lentigo is also characterized by deep epidermal invaginations that form club-shaped or bud-like extensions into the dermis.…”
Section: Mid- and Long-term Consequences Of Uv Exposurementioning
confidence: 75%
“…Such lentigo is also characterized by deep epidermal invaginations that form club-shaped or bud-like extensions into the dermis. Melanocyte activation is controversial, as their density along the dermal epidermal junction has been found to be similar in lesional compared to perilesional skin [ 310 , 311 ]. Of interest, transcriptomic studies revealed multiple molecular alterations notably dysregulation of keratinocyte proliferation and differentiation and modifications of the dermal extracellular matrix suggesting that keratinocytes and the dermal compartment could play a crucial role in the physiopathology of lentigines [ 310 , 311 , 312 ].…”
Section: Mid- and Long-term Consequences Of Uv Exposurementioning
confidence: 99%
“…Different authors could not find pigmentation genes differentially expressed in SL. In stead, genes which are involved in the keratinization process, such as SPRR4 [20] or LCE1E were detected, and sciellin was proved to be downregulated [20, 21]. Cario-Andre et al [22] proposed retaining perilesional pigment-harboring keratinocytes as a causative factor.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we focused on the genes highly expressed in each region (Supplementary Fig. 1c) (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). Genes encoding ELOVL fatty acid elongase and 5 (ELOVL3 and ELOVL5), perilipin 2 and (PLIN2 and PLIN5), and microsomal glutathione S-transferase 1 (MGST1) are highly expressed in sebaceous glands (23)(24)(25)(26).…”
Section: The Ssl-rna Expression Profile Predominantly Reflects Mrna Expression In Sebaceous Glands Epidermis and Hair Folliclesmentioning
confidence: 99%